Efeitos das contingências de reforçamento LAG e RDF sobre a variabilidade comportamental de crianças autistas - Sélios, Talita Lopes (2012)
In order to verify the effects of the reinforcement contingencies LAG and RDF on the behavioral variability of autistic children, was established in the present research two different teaching procedures of variability one for the LAG contingency and other for the RDF that started with low variation requirement to obtain reinforcement and consisted of gradual increasing in the variability exigency. So, the objective was to investigate if (1) the two reinforcement procedures contingent to the vary LAG and RDF of motor responses of autistic children, with gradual increasing in the exigency of variation, would produce a variable responding in computer games; and (2) occurred extension of acquired variability in the taught task with the LAG and RDF contingencies for the other tasks not submitted to the direct reinforcement of vary task with response topographically similar and task with response topographically different from the task that composed the experimental task. The six participants realized three computer games. They were exposed a baseline phase with each one of the tree games and, then, four of them were submitted to the training phase with the variability contingency with the Game 1 considering that for two of them, the teaching of the variability was given with the LAG contingency (the reinforce was presented if a determined sequence completed differed from last n completed sequences), and, for the other two, with the threshold contingency or frequency dependent reinforcement RDF (the reinforce probability was greater as lower was the relative frequency and the recency of a sequence) and two passed to training with the yoked contingency with the Game 1 (the reinforce distribution obtained in the procedure in which the variability was directly reinforced established what completed sequences would produce reinforces; the release of the reinforce was, therefore, independent of the responding being varied). In the end of each level that composed the teaching of variability and the yoked and after the teaching of the last level, extension tests of variability were realized one to the task topographically similar to teaching task (Game 2) and other to the task topographically different (Game 3). The results showed that the reinforcement contingencies LAG and RDF produced variability. The procedures of gradual increasing of exigency of variation, for both contingencies, generate variable responding and, in general, the higher was the requirement of variation, higher the variability. Both contingencies produced, in the end of the teaching process, high and similar variability levels. The yoked contingency did not alter the variability, permitting conclude that the variable responding generated for the LAG and RDF contingencies was due to the reinforcement contingent to vary and not of the intermittency among the reinforces. It was also verified that occurred extension of variability only to the task topographically similar to that taught and it could already be observed during the teaching process